2021
DOI: 10.3892/etm.2021.10263
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-200b-3p alleviates lipid accumulation and promotes cholesterol efflux by targeting ABCA1 in macrophage-derived foam cells

Abstract: Atherosclerosis (As) is a chronic cardiovascular disease characterized by abnormal of lipid accumulation and cholesterol efflux. The present study aimed to investigate whether the micro-RNA (miR)-200b-3p could exacerbate As by promoting lipid accumulation and inhibiting cholesterol efflux via ATP-binding cassette transporter A1 (ABCA1) in macrophage-derived foam cells. Blood samples from 30 patients with As and 30 healthy people were collected at Quanzhou First Hospital. RAW264.7 cells were used to establish f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…According to previous studies, carotid stenosis caused by carotid web lesions was a risk factor for the occurrence of TIA (Hu et al., 2019 ) and changes in miR‐200b‐3p expression were found in degenerative aortic stenosis patient tissues (Shi et al., 2016 ). Meanwhile, another study suggested a link between miR‐200b‐3p and lipid metabolism (Wu et al., 2021 ). Thus, it can be deduced that miR‐200b‐3p might be closely related with carotid stenosis and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to previous studies, carotid stenosis caused by carotid web lesions was a risk factor for the occurrence of TIA (Hu et al., 2019 ) and changes in miR‐200b‐3p expression were found in degenerative aortic stenosis patient tissues (Shi et al., 2016 ). Meanwhile, another study suggested a link between miR‐200b‐3p and lipid metabolism (Wu et al., 2021 ). Thus, it can be deduced that miR‐200b‐3p might be closely related with carotid stenosis and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al. ( 2021 ) has reported that the knockdown of miR‐200b‐3p alleviated lipid accumulation and promoted cholesterol efflux, which were two characteristics in the pathogenesis of atherosclerosis, by targeting ABCA 1 . Another study found that miR‐200b‐3p was involved in the regulation of angiogenesis by directly regulating the vascular endothelial growth factor (VEGF) signaling (Choi et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations